Legal Consequences of Fines for Street Vendors Through North Sumatra Provincial Regulation Number 35 of 2025 from the Perspective of Siyasah Qadhaiyyah (Case Study of North Labuhanbatu) - Imam Mashuri Nasution; Mhd Yadi Harahap (IHSA Institute, 2025)
This study aims to analyze the legal consequences of imposing fines on street vendors (PKL) in North Labuhanbatu Regency who sell on the roadside, viewed from the perspective of siyasah qadhaiyyah. This issue is important to study considering that many street vendors still violate the provisions of North Sumatra Provincial Regulation Number 35 of 2025, thus causing disturbances to public order. To obtain answers to the above problems, this study uses an empirical legal research type with a case study approach and statutory regulations. The data were collected through field observations and in-depth interviews with informants / respondents. The results of the study indicate that the imposition of fines has not fully complied with the provisions of the Regional Regulation, both in terms of amount and imposition procedures. From the perspective of siyasah qadhaiyyah, these sanctions must be implemented by considering the principles of benefit, proportionality, and justice so as not to cause greater harm to traders